22. CONGENITAL HEART DISEASES MODEL AT CHILDREN'S HOSPITAL 2 IN THE PERIOD 2018–2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the disease model, patient admission characteristics, treatment, and outcomes of congenital heart diseases (CHD) at Children’s Hospital 2 from 2018 to 2023.Method: A retrospective descriptive study was conducted based on medical records of inpatient CHD cases over a 6-year period. Epidemiological indicators, types of CHD, interventions, and treatment outcomes were analyzed by year.Results: A total of 11,508 inpatient CHD cases were recorded. Acyanotic CHDs accounted for 58% while cyanotic CHDs comprised 27.4%. The rates of interventional consultation, surgery, and catheterization increased annually, whereas the rate of conservative treatment declined. The average mortality rate was 3.33% and showed a downward trend. Cyanotic CHD patients were admitted at younger ages, had longer hospital stays, and higher mortality and discharge-against-advice rates compared to acyanotic cases.Conclusion: The CHD model at Children’s Hospital 2 has shown significant changes toward earlier diagnosis and more active intervention. The findings emphasize the importance of early screening, timely referral, and multidisciplinary coordination in managing severe CHD cases.
Keywords: Congenital heart diseases, disease model, Children’s Hospital 2